Teacher Performance Development Through Individual Ability, Self-efficacy, and innovation: Evidence from Public Elementary School in Peusangan District, Bireun Regency - Saiful Bahri; Iis Marshitah (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Teachers play a strategic role in improving educational quality through pedagogical, social, personal, and professional competencies. The swift evolution of education in the context of globalization and digitalization necessitates that educators exhibit elevated levels of personal competence, self-efficacy, and inventive conduct. This study seeks to examine techniques for enhancing teacher performance based on individual capability, self-efficacy, and innovation in public elementary schools within the Peusangan District of Bireuen Regency. The research utilized a mixed-methods approach with a sequential explanatory design. Quantitative data were gathered via surveys and analysed using path analysis and SITOREM (Scientific Identification Theory for Operational Research in Education Management), while qualitative data were acquired through interviews, observations, and documentation to enhance quantitative results. The sample comprised teachers from 28 public primary schools, with 147 participants chosen via Slovin’s algorithm. The results demonstrate that personal capability, self-efficacy, and inventive conduct substantially enhance teacher performance. Educators possessing elevated self-efficacy exhibit increased initiative in fostering instructional innovation and adjusting to curriculum modifications. Nonetheless, various indices of innovation and human capability remain inadequate, especially in the exploration of novel teaching tactics and problem-solving methodologies. The study advocates for the fortification of professional development programs, the augmentation of teacher confidence, and the promotion of innovation-driven learning methodologies to elevate teacher performance and educational quality.